Die deutsche Fischerei auf Köhler 1989 im Nordost-Atlantik - Reinsch, H.H. (1990)
Johann Heinrich von Thünen-Institut, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung = Information on Fishery research in 2010